(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
Objective: Craniovertebral junction (CVJ) anomalies with functional instability represent a complex pathology in neurosurgical practice, often leading to spinal cord compression, vascular compromise, and significant neurological deficits. This study aims to improve surgical outcomes by developing a diagnostic algorithm based on neuroimaging criteria to guide the selection of surgical intervention.